Turnover and retention of Catholic school superintendents in the United States: averting a crisis. Issue 2 (3rd July 2022) - Cook, Timothy; Fussell, Ronald; Simonds, Thomas
Abstract : Stability of leadership in Catholic education at the (arch)diocesan level is essential for achieving school system wide goals. This study investigated turnover and retention of Catholic school superintendents in the USA. Ten former superintendents were interviewed. The interview findings revealed that all but one former superintendent had left their positions earlier than planned. Their major reason for leaving early was related to negative experiences with church bureaucracy and politics at the head offices of their respective (arch)dioceses. To increase retention, the authors recommend a two-year induction process that includes a well-thought-out orientation, mentoring, provision for spiritual support, and access to tailored professional development. The authors also recommend these system-level changes: an overhauled preparation programme for superintendents, new organisational practices in the diocesan main office (i.e. chancery), clear succession plan, and national standards to guide consistent implementation of these changes.